سوق الأوراق المالية ودوره في النمو الاقتصادي - نور الهدى, دحماني; شريفة, العابد برينيس (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(--scale-factor)*68.06px); top: calc(var(--scale-factor)*542.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999755);" role="presentation">The stock market plays a strategic and an important role in the relaunch of economic growth. It <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*555.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955773);" role="presentation">constitute channels through which the flow of funds from <span dir="ltr" style="left: calc(var(--scale-factor)*294.79px); top: calc(var(--scale-factor)*555.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962655);" role="presentation">the surplus units to the deficit units. Also, the <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*568.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933485);" role="presentation">stock market mobilizes and channels savings and financial resources to the most productive investments <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*581.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908367);" role="presentation">consequently contributes to puch the economic growth. <span dir="ltr" style="left: calc(var(--scale-factor)*68.06px); top: calc(var(--scale-factor)*595.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972783);" role="presentation">In this context, we’ll try, through this study t<span dir="ltr" style="left: calc(var(--scale-factor)*252.29px); top: calc(var(--scale-factor)*595.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927523);" role="presentation">o demostrate the role of stock market, and determine the <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*608.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921816);" role="presentation">causal relationship that exists between them in Indonesia and Algeria during thr period (1999-<span dir="ltr" style="left: calc(var(--scale-factor)*434.38px); top: calc(var(--scale-factor)*608.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931552);" role="presentation">2011), using <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*621.67px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908793);" role="presentation">Granger causality test and Vector Auto regressive model. <span dir="ltr" style="left: calc(var(--scale-factor)*68.06px); top: calc(var(--scale-factor)*634.87px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933007);" role="presentation">This study has concluded the <span dir="ltr" style="left: calc(var(--scale-factor)*192.41px); top: calc(var(--scale-factor)*634.87px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950368);" role="presentation">existence of causal relationship in one direction from the stock market <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*648.07px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914303);" role="presentation">according market capitalization ratio index to the economic growth in the case of Indonesia. In contrast, the <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*661.42px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918958);" role="presentation">causal relationship is not verified in the case of Algeria.